Enhancing Online Meeting Adoption Among Chengdu’s Youth - Xu, Kairong (Scholar: Human Sciences, 2025)
Purpose: The purpose is to identify the determinants of young people’s satisfaction, perceived usefulness, and continued intention to use online meetings in Chengdu, China. This study proposed a conceptual framework in which the factors were hypothesized to have causal relations among Confirmation, Satisfaction, Usefulness, Informational Support, Network Management, Emotional Support, Effort Expectancy, and Continuance Intention. Research Design, Data, and Methodology: The quantitative methodology of this study uses a sample size of 500, with a survey instrument administered to gather data from the target population. The questionnaires were distributed among all eligible individuals in seven major districts of Chengdu. Data analysis used Confirmatory Factor Analysis and Structural Equation Modeling to validate the model fit and confirm the causal relationships among the variables. Results: Satisfaction and usefulness were two fundamental predictors and antecedents of continuance intention in online meetings. All nine proposed hypotheses were confirmed and aligned with the study objectives. Conclusions: Six of the eight hypotheses were supported by the research objectives. Developers of online meeting systems and organizers concerned about users’ engagement in using them should pay attention to improving the quality factors of online meetings so that a positive attitude development and behavioral intentions can be fruitful.